'We need to make sure that we are always something else': Victim support organisations and the increasing responsibility of the state in supporting crime victims in Finland and Norway. Issue 2 (May 2019) - Helminen, Maija
In response to international obligations many Western states have strengthened their responsibility for crime victims' access to support services. This is also the case in Finland and Norway where this interview study explored the views of representatives from five key civil society organisations (CSOs) working with victims of crime in relation to the public sector's increasing duty to organise victim support services. The findings indicate that despite the fact that improvements in victims' access to support services were generally welcomed, there was a growing concern that the position of these traditional CSOs could – or already had – become challenged by the public and private organisations and other CSOs as new funding streams and mechanisms attract new players to the field. This had created a need to highlight the distinctiveness of these agents as CSOs working with victims of crime. This article argues that while international standards for victim support services have been a triumph for victim movements in many countries, their realisation in the present era of austerity and mixed welfare economies presents traditional victim support organisations with new challenges in retaining their ownership and distinctive ways of treating the problem of victimisation.